Functional Analysis of the Endopeptidase and Holin From Planktothrix agardhii Cyanophage PaV-LD - Meng, Li-Hui; Ke, Fei; Zhang, Qi-Ya; Zhao, Zhe (Frontiers in Microbiology, 2022)
A cyanophage PaV-LD, previously isolated from harmful filamentous cyanobacterium Planktothrix agardhii, was sequenced, and co-expression of its two ORFs in tandem, ORF123 and ORF124, showed the growth inhibitory on the model cyanobacterium Synechocystis sp. PCC6803 cells. However, the mechanism of action of ORF123 and ORF124 alone remains to be elucidated. In this study, we aimed to study the individual function of ORF123 or ORF124 from PaV-LD. Our data showed that the ORF123 encoded an endopeptidase, which harbored an M23 family peptidase domain and a transmembrane region. Expression of the endopeptidase in E. coli alone revealed that the protein exhibited remarkable bacteriostatic activity, as evidenced by observation of growth inhibition, membrane damage and leakage of the intracellular enzyme. Similarly, the holin, a membrane-associated protein encoded by the ORF124 showed weak bacteriostatic activity on E. coli. Moreover, deletion mutations indicated that the transmembrane domains of endopeptidase and holin were indispensable for their bacteriostatic activity. Meanwhile, the bacteriostatic functions of endopeptidase and holin on cyanobacteria cells were confirmed by expressing them in the cyanobacterium Synechocystis sp. PCC6803. Collectively, our study revealed the individual role of endopeptidase or holin and their synergistic bacteriolytic effect, which would contribute to a better understanding of the lytic mechanism of cyanophage PaV-LD.